THE PRODROMES OF THE MEDIEVAL AND MODERN PROVIDENTIALISM VIEW OF DISASTER: A HISTORICAL AND CULTURAL STUDY THROUGH THE 18TH CENTURY BC. AND THE 13TH CENTURY A.D. - De Nardi, Loris; Cordero Fernández, Macarena (Revista de Historia Social y de las Mentalidades, 2022)
The Historical Study of Disasters has shown that the origin of earthquakes, epidemics, floods, among others, does not lie in the natural or biological phenomenon itself but should be considered as the result of the vulnerability of a community to a certain threat. This article will present the studies related to disasters and their management that have carried out in recent decades, in what way and through what process they have conceptualized the social construction of risk and vulnerability, intending to compare this conceptualization with the providential vision of the disaster, and what was the social and cultural perception of disasters, starting from the ancient-medieval cosmogony, which lasted until modernity.
Keywords: History of Disasters; Vulnerability; Social Construction of Risk; Providential vision of the disaster